2003
DOI: 10.1080/14445921.2003.11104147
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensions of Human Action and Property

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is hard to conceive of governments or corporations as such being happy, although the actions they take can affect human happiness a great deal, independent of the GNP they generate, the taxes they collect, and the shareholder wealth they create. The cultural aspects of property are diverse and worthy of further study (Small, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to conceive of governments or corporations as such being happy, although the actions they take can affect human happiness a great deal, independent of the GNP they generate, the taxes they collect, and the shareholder wealth they create. The cultural aspects of property are diverse and worthy of further study (Small, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the law, Small (2003) argued that law itself rested on foundations that included cultural, ethical, anthropological, theological and metaphysical conclusions that all contributed to the institution of property. This would suggest that a thorough understanding of the operation of property economics in a particular institutional context could be informed by methodological approaches employed by any of these sciences.…”
Section: Emerging Methodologiesmentioning
confidence: 99%
“…Underlying the question of value is the question of property rights (Small 2003). What is generally accepted in western societies as property ownership is relatively young in historical terms, being largely a creature of modernity and progressively taking form through the modern era, that is, from Machiavelli (d. 1527) onwards.…”
Section: Property Rights and Valuementioning
confidence: 99%
“…Small (2003) demonstrated that property economics continues to be best understood as built upon a cultural/moral base and the reluctance of western users of property to do this is largely responsible for the difficulties encountered in relating to customary property rights. The Aristotelian/Thomistic approach to the institution of property is built on considerations of the good of the community as the justification of private property itself and this approach would have been familiar to Tom Whipple, and apparently valued by him as evidenced in his contribution to preserving Dr. Woodbury's work.…”
Section: Land Value and Quality Of Lifementioning
confidence: 99%